The position of social networks and messengers in the information space of Belarus - Kudrevich, Maxim A.; Shkurova, Alena V. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article analyses various aspects of digital communication. The concept of information space is defined. The structure of Internet users is considered based on sociological study of the population by the Institute of Sociology of the National Academy of Sciences of Belarus. The main actors of the information space in Belarus are singled out. The role of the Internet in the space of media consumption is determined. The conclusion about the predominance of new media (Internet resources, social networks and instant messengers) in the information field is made. The age specificity of media consumption is analysed. The main problems of mastering digital technologies by representatives of the older age group are highlighted. The problem of the intersection of the semantic fields of the older and younger age groups is explicated due to the use of various information sources. The Internet space is considered as a phenomenon that claims to have an independent reality. The devices that provide access to the Internet are described. Mobility of connection and constant access to up-to-date information are presented as characteristics that ensure the rapid spread of network technologies among the economically active population. The data of the study of the Institute of Sociology of the National Academy of Sciences of Belarus and the international study DataReportal are compared. The difference of methodological approaches to media measurement is analysed. The place of social networks and messengers is considered in the structure of media consumption, and the popularity of individual social networks and messengers among the population of Belarus is analysed, taking into account age differences. The general specificity of the Internet space of Belarus is determined.